Stable incidence but declining case-fatality rates of subarachnoid hemorrhage in a population. (22nd November 2016) - Mackey, Jason; Khoury, Jane C.; Alwell, Kathleen; Moomaw, Charles J.; Kissela, Brett M.; Flaherty, Matthew L.; Adeoye, Opeolu; Woo, Daniel; Ferioli, Simona; De Los Rios La Rosa, Felipe; Martini, Sharyl; Khatri, Pooja; et al.
Abstract : Objective: To characterize temporal trends in subarachnoid hemorrhage (SAH) incidence and outcomes over 5 time periods in a large population-based stroke study in the United States. Methods: All SAHs among residents of the Greater Cincinnati/Northern Kentucky region at least 20 years of age were identified and verified via study physician review in 5 distinct year-long study periods between 1988 and 2010. We abstracted demographics, care patterns, and outcomes, and we compared incidence and case-fatality rates across the study periods. Results: The incidence of SAH in the 5 study periods (age-, race-, and sex-adjusted to the 2000 US population) was 8.8 (95% confidence interval 6.8–10.7), 9.2 (7.2–11.2), 10.0 (8.0–12.0), 9.0 (7.1–10.9), and 7.7 (6.0–9.4) per 100, 000, respectively; the trend in incidence rates from 1988 to 2010 was not statistically significant ( p = 0.22). Advanced neurovascular imaging, endovascular coiling, and neurologic intensive care unit availability increased significantly over time. All-cause 5-day (32%–18%, p = 0.01; for trend), 30-day (46%–25%, p = 0.001), and 90-day (49%–29%, p = 0.001) case-fatality rates declined from 1988 to 2010. When we included only proven or highly likely aneurysmal SAH, the declines in case-fatality were no longer statistically significant. Conclusions: Although the incidence of SAH remained stable in this population-based region, 5-day, 30-day, and 90-day case-fatality rates declined significantly. Advances in surgical and medical management, along with systems-based changes such as the emergence of neurocritical care units, are potential explanations for the reduced case-fatality.